Mathematical Models of Electrical Network Systems: Theory and Applications - An Introduction - Klos, Andrzej (Lecture Notes in Electrical Engineering, 2017)
This work is for all those who are looking for a non-conventional mathematical model of electrical network systems. It presents a modern approach using linear algebra and derives various commonly unknown quantities and interrelations of network analysis.